Construction of a prognostic survival model for colorectal cancer patients using CT image texture analysis: a prospective cohort study - Sun, Chen-hua; Wang, Hao-di; Sun, Wen-hao; Gong, Guan-wen; Deng, Zheng-ming; Jiang, Zhi-wei (Frontiers in Oncology, 2026)
BackgroundCurrent prognostic indicators for colorectal cancer are limited to pathological staging, which offer only modest predictive value. This study aims to develop a prognostic prediction model for colorectal cancer patients based on texture analysis (TA), with the goal of forecasting long-term survival outcomes.MethodsA total of 236 patients underwent abdominal CT scanning, including both unenhanced and contrast-enhanced CT. Using MaZda software, regions of interest (ROIs) were identified, and texture features were extracted. These texture features were combined with pathological staging data, and statistical analyses were performed using Cox regression, Lasso regression, nomograms, forest plots, receiver operating characteristic (ROC) curve analysis, and survival analysis (Kaplan-Meier curves), and carry out the validation work of the external validation set.ResultsObservation points were established at 1, 3 and 5 years. A correlation analysis was conducted using patient demographic data, tumor markers, pathological staging, and more than 300 variables derived from the texture analysis. The analysis revealed correlations between texture features (such as Teta1, Teta4, WavEnLL_s-2, GrSkewness, and Horzl_RLNonUni) and survival time. Nomograms were created to provide a rough estimation of patient survival, which could assist in decision-making for subsequent treatment plans. Using Lasso regression combined with the nomogram for dimensionality reduction, we were able to intuitively assess the predicted five-year survival time for patients in the perioperative period.ConclusionRadiomics analysis of colorectal cancer, when combined with traditional TNM staging, can aid in the construction of a survival prediction model. This model may offer novel insights for predicting long-term survival and provide a reference for the development of individualized treatment strategies.Clinical trial registrationhttps://www.chictr.org.cn/showproj.html?proj=185835, identifier ChiCTR2200065942.